An innovative magnetic oxide dispersion-strengthened iron compound obtained from an industrial byproduct, with a view to circular economy (2020)
Since the policy of Sustainable Production and Consumption has laid the basis for the world to begin its transition towards a circular economy, engineering has a moral responsibility to recycle industrial byproducts. This is currently done with calamine, which is a mill scale resulting from high temperature steel manufacturing. Although calamine is used in different ways, it could be given greater added value by subjecting it to processing by powder metallurgy. Therefore, the aim of this study was to obtain powder from iron with a core of enriched magnetite iron oxide, and to evaluate the effect of this iron oxide nucleus on the hardness and magnetic properties of the material after sintering. It was found that iron oxide acts as a reinforcement for iron (the highest achieved hardness was 77.7 ± 1.2 HRB) due, in part, to the coherency between phases, and confers a ferrimagnetic behavior to it. Therefore, this material has potential for use in magnetic applications at higher frequencies than current soft materials.